Brand Image: As a Mediating Variable in the Relationship between E-WOM and Repurchase Intention of Teh Botol Sosro Products - Achmad Abyan Zharfan; Nuruni Ika Kusuma W (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research examines the influence of e-WOM and Brand Image on repurchase intention, and the mediating effect of Brand Image on the relationship between e-WOM and repurchase intention. Using a quantitative approach and non-probability sampling, data from 100 Tehbotol Sosro's consumers were analyzed with SmartPLS 3.0 software. The findings indicate that e-WOM positively and significantly affects repurchase intention and Brand Image. Brand Image also positively and significantly affects repurchase intention, acting as a mediator between e-WOM and repurchase intention